The Role of Influencer Credibility in Shaping Generation Z Purchase Decisions: Evidence from Traditional Cosmetic Brand Repositioning - Fadhilah; Galih Ginanajar Saputra; Arum Wahyuni Purbohastuti (SAFE-Network, 2026)
The rapid growth of social media has transformed marketing communication strategies, particularly in engaging Generation Z consumers. This study aims to examine the role of influencer credibility comprising trustworthiness, expertise, and attractiveness in shaping parasocial interaction and its impact on purchase decision within the context of traditional cosmetic brand repositioning. Specifically, this research focuses on the collaboration between Puteri Indonesia influencers and Mustika Ratu on Instagram. A quantitative approach was employed using a survey method with purposive sampling, involving Generation Z respondents who actively use Instagram and have been exposed to influencer marketing content. The data were analyzed using Partial Least Squares Structural Equation Modeling. The results reveal that all dimensions of influencer credibility have a positive and significant effect on both parasocial interaction and purchase decision. Furthermore, parasocial interaction demonstrates a strong influence on purchase decision and serves as a significant mediating variable in the relationship between influencer credibility and purchase decision. These findings highlight that influencer effectiveness is not solely determined by credibility in delivering information but also by the ability to build emotional connections with audiences. The study contributes to the literature by integrating source credibility and parasocial interaction theories in the context of digital marketing and provides practical insights for brands in selecting credible influencers and designing engagement-driven content strategies.